Dimensions of personality, multiple intelligences, learning styles, motivation for academic achievement and its relationship to academic achievement - Jabr, Luay Khazal (Al-Adab Journal, 2015)
Current study aimed : (1) recognition relationships among Five Factor of Personality , Multiple Intelligences , Learning Styles , Academic Achievement Motivation , and Academic Achievement , (2) measure ability of Five Factor of Personality , Multiple Intelligences , Learning Styles , Academic Achievement Motivation , Gender and Father and Mother Achievement to predicted Academic Achievement . applied seven scales : NEO-PI-R , MIDAS , LSS , ILS , AMS , IOAM-SOAM , and SAM , on student sample consist of 94 male and female . After data analysis , appear there is significance positive correlation between Academic Achievement and : Conscientiousness and Achievement Striving , ideas , logical Intelligence , Independence and Learning Styles , and Cognition , and significance negative correlation with Natural Intelligence and Avoidant and Global Learning Styles . By use stepwise multiple regression analysis , defined five significance predictors to Academic Achievement : Independence Style , Conscientiousness , Achievement Striving , logical Intelligence and cognition . Depend on this results , formulated " Social Scientific Academic Achievement Model for Iraqi Student " , and presented some recommendations and suggestions